Legal Protection for Customary Land Disputes of Customary Law Communities in West Papua for the Auwyu Tribe from the Perspective of Legal Pluralism - Yusefin Dellyana K (Publikasi Indonesia, 2025)
Legal protection for customary land in Papua, particularly West Papua, is a crucial issue reflecting the tension between state law and customary law. The transfer of customary land from customary law communities to agencies or corporations is a dispute that must be faced and is inevitable when faced with realities such as the massive granting of environmental permits, as happened to the Auwyu tribe in Boven Digoel Regency, South Papua Province. Although state law as regulated in Article 18B paragraph (2) of the 1945 Constitution, the Basic Agrarian Law, and Law Number 21 of 2001 concerning Special Autonomy for Papua Province has recognized the existence and rights of customary law communities, its implementation has not fully provided a guarantee of effective protection when juxtaposed with state law that allows customary land management for parties other than customary law communities. This study aims to analyze the form of legal protection for customary land and evaluate the mechanism for resolving customary land disputes in Boven Digoel Regency, West Papua Province for the Auwyu tribe from the perspective of legal pluralism. This study uses a socio-legal approach with a normative basis in the applicable state law that regulates customary law communities, customary land, and customary land dispute resolution, combined with empirical data on the settlement of customary land disputes of the Auwyu tribe. The theory of legal pluralism is used as a conceptual and critical analysis tool to assess the legal problems in the study.